2021
DOI: 10.3389/fgene.2021.698046
|View full text |Cite
|
Sign up to set email alerts
|

Whole Transcriptome Analysis Revealed a Stress Response to Deep Underground Environment Conditions in Chinese Hamster V79 Lung Fibroblast Cells

Abstract: Background: Prior studies have shown that the proliferation of V79 lung fibroblast cells could be inhibited by low background radiation (LBR) in deep underground laboratory (DUGL). In the current study, we revealed further molecular changes by performing whole transcriptome analysis on the expression profiles of long non-coding RNA (lncRNA), messenger RNA (mRNA), circular RNA (circRNA) and microRNA (miRNA) in V79 cells cultured for two days in a DUGL.Methods: Whole transcriptome analysis including lncRNA, mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
1
6
1
Order By: Relevance
“…CDH1, known as a tumor suppressor, is implicated in maintaining genomic stability and restraining cancer progression, which was highly expressed in FD-LSC-1 cells underground ( 30 ). Notably, unlike our preliminary observation of V79 cells ( 29 ), most of the enriched candidates were up-regulated, whereas only the expression level of BCL2 binding component 3 (BBC3 ), Wnt6 , and BMP2 were decreased in the Hippo signaling pathway. Exposure to ionizing radiation can induce transcription of BBC3 , causing cell apoptosis in response to DNA-damaging stimuli ( 31 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…CDH1, known as a tumor suppressor, is implicated in maintaining genomic stability and restraining cancer progression, which was highly expressed in FD-LSC-1 cells underground ( 30 ). Notably, unlike our preliminary observation of V79 cells ( 29 ), most of the enriched candidates were up-regulated, whereas only the expression level of BCL2 binding component 3 (BBC3 ), Wnt6 , and BMP2 were decreased in the Hippo signaling pathway. Exposure to ionizing radiation can induce transcription of BBC3 , causing cell apoptosis in response to DNA-damaging stimuli ( 31 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In the BP category, up-regulation of coding genes were mainly enriched in biological regulation and response to stimulus, indicating that these genes may be potentially targeted for stress responses and cell growth. Similar to our previous study, significant enrichment in metabolic process categories was detected among identified DE lncRNAs ( 29 ). Consistent with the above, modification process, cellular response to stress, and the cell cycle were representative items of the host genes of circRNAs, which implied interactions with mRNAs and lncRNAs under an ionizing radiation-deprived environment.…”
Section: Discussionsupporting
confidence: 88%
“…Liu et al showed that V79 and FD-LSC-1 cells, when cultivated in a DUL, had hypertrophic ER, obvious Golgi bodies, and downregulation of major ER stress proteins (WFS1, STT3B, CANX, ERP29, and HSPA5) compared to cells cultured above ground ( 46 , 47 ). Transcriptomics demonstrated that differently expressed (DE) circRNAs in V79 cells cultured in the DUL or above ground were predominantly enriched in genes associated with protein processing in the endoplasmic reticulum ( 19 ).…”
Section: Biological Research In the Dugementioning
confidence: 99%
“…Altered RNA profiles in lncRNAs, mRNAs and circRNAs. Differentially expressed RNAs involved in many pathways including ECM-RI, PI3K-Akt signalling, RNA transport and the cell cycle Cell growth inside DUL could induce transcriptional repression, thus reducing metabolic process and reprogramming the overall gene expression profile in V79 cells Duan et al ( 2021 ) A11 mouse hybridoma cells Underground vs above ground environment (LNGS, Italy) Inside DUL: ~ 10 –6 —~ 10 –5 mGy/h (inside a shielded or an unshielded incubator) Cell proliferation, caspase-3 activation and PARP1 cleavage (western blot) (4 weeks of continuous culture in different environments plus 2 weeks above ground) No differences in cell proliferation; switch of the over-growth-induced cell apoptosis to autophagy underground, Caspase-3 activation and PARP1 cleavage in cells entering in over-growth status above ground only; p53 activation underground; scarce influence of further gamma ray shielding underground Fischietti et al ( 2020 ) Chinese hamster V79 cells Underground vs above ground environment (LNGS, Italy) Inside DUL: ~ 10 –6 mGy/h Gene expression (RT-qPCR) and activities of antioxidant enzymes (GPX, SOD, CAT) (10 months of continuous culture in different environments plus 6 months above ground) Higher degree of defence against endogenous damage in reference conditions: GPX activity significantly decreased underground and remaining at the same level even after further 6 months above ground Fratini et al ( 2015 ) Zebrafish AB strain γ-irradiation Doses: 5.2, 31 Gy Dose rates: 8.7 and 53 mGy/h Mating, gene expression, health parameters. (month or years later), health of F1 Few genes in F1 from different doses overlapping, more overlapping between higher dose 1-month F1 and lower dose 1-year F1 Hurem et al ( 2018 ) Mouse C57Bl/6 γ-irradiation Doses: 3 × 10 2 , 6 × 10 3 mGy Dose rates: 0.042 and 0.83 mGy/h Gene expression analysis (after 300 days of exposure) Differentially expressed gene lists according to dose rate Kempf et al ( 2016 ) Chinese hamster V79 cells FD-LSC-1 Laryngeal Squamous Carcinoma Cells …”
Section: Experimental Evidence Of a Dose Rate Effectmentioning
confidence: 99%